Local Wisdom Meets Digital Pedagogy: Integrating Indonesian Art into Online Language Learning - Yan Nurcahya (International Journal of Digital Learning on Languages and Arts, 2025)
This study examines the implementation of local wisdom–based digital pedagogy in online language learning among university students in Indonesia. As higher education increasingly adopts digital platforms, integrating cultural and artistic elements becomes essential to create meaningful and contextually relevant learning experiences. Using a qualitative descriptive approach, this research investigates how Indonesian art such as batik motifs, traditional songs, and folklore narratives can be incorporated into digital language learning activities for students. Data were obtained through virtual classroom observations, student reflections, and interviews with lecturers. The findings indicate that the integration of local art forms enhances students’ motivation, intercultural awareness, and linguistic competence. Moreover, digital tools enable learners to reinterpret traditional art through multimedia projects, promoting creativity and collaboration in online learning environments. This study concludes that embedding Indonesian local wisdom into digital pedagogy not only strengthens cultural identity among university students but also provides an innovative framework for inclusive and culturally grounded language education in the digital era.   Keywords: digital pedagogy, local wisdom, university students, Indonesian art, online language learning